Luminescence lineshapes of nitrogen vacancy center in lonsdaleite and dual structure of diamond/lonsdaleite: a DFT study - Khaled A. Abdelghafar; Daniel S. Choi; Khalid A. Askar (Scientific Reports)
Abstract Lonsdaleite is a metastable hexagonal allotrope of carbon, which outperforms cubic diamond in terms of mechanical properties. Here, we investigate nitrogen vacancy center (NV) in pure lonsdaleite as well as the dual structure of diamond/lonsdaleite using the density functional theory (DFT). By examining various nitrogen vacancy (NV) center configurations, it was found that off-c-axis defects exhibit distinct elongation in certain bonds and localized strain, leading to shifts in electronic states and stronger electron-phonon interactions. Luminescence analysis highlights differences in zero-phonon line weights, indicating varied dominance of phonon side bands. Furthermore, the findings assert that NV0 and NV− 1 centers in lonsdaleite demonstrate the existence of two non-degenerate excited states (ex & ey) for the off-c-axis defect as a result of C1h symmetry evolution instead of C3v symmetry. Surprisingly, the findings demonstrate that the zero-phonon line (ZPL) falls around ~ 2.38 eV for NV0, which agrees with the reported ZPL of 2.32 eV for NV0 in lonsdaleite from meteorites. Thereby, the current model could interpret the experimental luminescence data of diamond/lonsdaleite dual structure.